A genome-wide search for determinants of survival in 1926 patients with advanced colorectal cancer with follow-up in over 22, 000 patients. (December 2021) - Wills, Christopher; He, Yazhou; Summers, Matthew G.; Lin, Yi; Phipps, Amanda I.; Watts, Katie; Law, Philip J.; Al-Tassan, Nada A.; Maughan, Timothy S.; Kaplan, Richard; Houlston, Richard S.; Peters, Ulrike; et al.
Abstract: Background: While genome-wide association studies (GWAS) have identified germline variants influencing the risk of developing colorectal cancer (CRC), there has been limited examination of the possible role of inherited variation as a determinant of patient outcome. Patients and methods: We performed a GWAS for overall survival (OS) in 1926 patients with advanced CRC from the COIN and COIN-B clinical trials. For single nucleotide polymorphisms (SNPs) showing an association with OS ( P < 1.0 × 10 −5 ), we conducted sensitivity analyses based on the time from diagnosis to death and sought independent replications in 5675 patients from the Study of Colorectal Cancer in Scotland (SOCCS) and 16, 964 patients from the International Survival Analysis in Colorectal cancer Consortium (ISACC). We analysed the Human Protein Atlas to determine if ERBB4 expression was associated with survival in 438 patients with colon adenocarcinomas. Results: The most significant SNP associated with OS was rs79612564 in ERBB4 (hazard ratio [HR] = 1.24, 95% confidence interval [CI] = 1.16–1.32, P = 1.9 × 10 −7 ). SNPs at 17 loci had suggestive associations for OS and all had similar effects on the time from diagnosis to death. No lead SNPs were independently replicated in the meta-analysis of all patients from SOCCS and ISACC. However, rs79612564 was significant in stage-IV patients from SOCCS ( P = 2.1 × 10 −2 ) but not ISACC ( P = 0.89) and SOCCS combined with COIN and COIN-B attained genome-wide significance ( P = 1.7 × 10 −8 ). Patients with high ERBB4 expression in their colon adenocarcinomas had worse survival (HR = 1.50, 95% CI = 1.1–1.9, P = 4.6 × 10 −2 ). Conclusions: Genetic and expression data support a potential role for rs79612564 in the receptor tyrosine kinase ERBB4 as a predictive biomarker of survival. Highlights: A genome-wide search for biomarkers of survival in 1926 patients with advanced CRC. Seventeen potential prognostic variants with replication of rs79612564 in ERBB4. A median decrease in life expectancy of ∼40 days per allele carried. Patients with high ERBB4 expression in colon tumours had worse survival. Potential use for rs79612564 and/or ERBB4 as a prognostic biomarker.